Pengaruh Minat Membaca dan Penguasaan Kosakata terhadap Ketrampilan Berbicara Bahasa Inggris Siswa (SMK) di Kecamatan Baso, Sumatera Barat - Edri Edri (Universitas Indraprasta PGRI Jakarta, 2019)
The research aims to analyze and discuss hypotheses regarding reading interest and word acquisition for the ability to speak English. The research hypothesis: Regarding interest in reading and mastery of shared words for English speaking skills. Related to interest in speaking in English, related mastering vocabulary words in English speaking skills grade. The research method used was a survey method with multiple regression analysis. The population of this research are students SMK Kec Baso Sumatera Barat Grade X. The results consider the fact that shows a significant interest in reading and vocabulary mastery in English speaking ability. This research summary is a positive publication of Interest in Reading and Vocabulary Mastery on the Capabilities of students.